A DESCRIPTION OF DONOR KNOWLEDGE ABOUT BLOOD DONOR AT THE INDONESIAN RED CROSS BLOOD DONOR UNIT, SLEMAN REGENCY - Tasya Karolina (Jurnal Ilmiah Cerebral Medika, 2021)
Background: Blood donation is the process of taking blood from donors who pass the donor selection. Blood donation can be done in the Blood Transfusion Unit (UTD) building or in another building during the Mobile Unit (MU). At the time of blood collection, attention must be paid to the safety of blood donors, especially regarding the amount of blood and the time of blood collection and the process must also be well documented (PMK 91, 2015) Objective: To find out the description of donor knowledge at the Indonesian Red Cross Blood Donor Unit, Sleman Regency Method: The research design used descriptive research methods. The research sample amounted to 84 donors at the PMI Blood Donor Unit, Sleman regency. Samping use is accidental samping. Collecting data in the form of a questionnaire.Results: The results showed that the results showed that the majority of respondents in this study had good knowledge, namely 41 people or 48,81%, moderately knowledgeable, namely 37 people or 44,05% while those with less knowledge were 6 people or 7,14%. Conclusions: The level of knowledge of donors at the Indonesian Red Cross blood donors as many as 41 people (48,8%) were categorize as good, 37 people (44,5%) were categorized as moderate, and 6 people (7,14%) is categorized as less.